ISTIHALAH ISSUE OF HALAL FOOD, MEDICINE, AND COSMETICS - Ratna Wijayant; M. Elfan Kaukab (Journal of Islamic, Social, Economics and Development, 2019)
Debates over halal and haram status of food, beverages, medicines, and cosmetics have heated recently. In the eye of Islamic law, something that is originally pure but is stained can be purified back by washing away the stain. One of the ways to do this is Istihalah (change of form). Istihalah can be defined as the change of form by mixing the matter with other substance to create a new product that has different form and content. The first to extend its usage is Hanafi Maliki Ibn al-‘Arabi madhab, Ibn Taymiyyah madhab, Ibn al-Qayyim, al- Syawkani, and Ibn Hazm al-Zahiri madhab. They put into practice istihalah theory in more general scope. Both Al-Hanafiyah and Al-Malikiyah madhab state that istihalah changes impure matter into pure matter. This is the more appropriate notion related to present era. On the other hand, both Asy-Syafi’iyah and Al-Hanabilah madhab insist that najis ‘ain, such as pig, cannot be eradicated even after undergoing total changes, unless when there are three exceptions. Hambali madhab hold the notion that one impure matter cannot be changed into pure one by istihalah process, except arrack that changes into vinegar by itself. Changes by means of burning, tanning, and mixing with other substances are not purifying. Based on the opinions given by Islamic scholars in extending or narrowing the istihalah concept, it is deduced that Hanafi madhab scholars’ notion is more relevant in being applied as it is in accordance with the reality. This notion is rational and harmoniously conforming to science and technology rapid development. A number of research and finding have been conducted, and new issues have developed in producing food.